Creation and Investigation of a Big Data Technology-Driven Auxiliary Employment Platform for Public Utilities Management - Lan, Zhijie (International Journal for Applied Information Management, 2023)
With the development of society and the advancement of science and technology, the current employment problem has gradually become hotter. At the same time, the number of college graduates has shown rapid growth. However, due to the development of science and technology in our country, the demand for labor has declined, and various factors have caused college students to find themselves in a difficult situation.The purpose of this article is to conduct research on the design of a public utility management assisted employment platform based on big data technology. Based on the analysis of the employment history and current situation of college students in New China, this paper analyzes the employment dilemma of college students from the perspective of "New Public Management", applies the concept of new public management to the public service platform of college student employment, and proposes that college students should be further improved. The degree of marketization of employment, the construction of a diversified employment service platform for college students, etc.Further clarify the focus of solving the employment problem of college students. Due to the theoretical and practical deficiencies of the new public management itself, the employment platform for college students derived from the perspective of the new public management has deficiencies. The experimental research results show that the effectiveness of the auxiliary employment platform for public utilities management is better is the auxiliary employment platform C for public utilities management, with an effectiveness of 75.83%. In general, the effective average of the auxiliary employment platform for public utilities management is 70. It can be seen that the actual use of these auxiliary employment platforms is not large, and at the same time, it also shows that there is a lot of room for.